2016
DOI: 10.2220/biomedres.37.299
|View full text |Cite
|
Sign up to set email alerts
|

<b>ATP release from bladder urothelium and serosa in a rat model of partial bladder outlet </b><b>obstruction </b>

Abstract: Overactive bladder is one of the major health problem especially in elderly people. Adenosine triphosphate (ATP) is released from urinary bladder cells and acts as a smooth muscle contraction and sensory signal in micturition but little is known about the role of ATP release in the pathophysiology of overactive bladder. To assess the relationship between ATP and overactive bladder, we used a partial bladder outlet obstruction (pBOO) model in rats. The bladder caused several changes by pBOO: An increase in blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…If the inflammation-driven damage to the bladder reaches a state where fibrosis and nerve damage occur, symptoms can persist even after removal of the obstruction via surgical intervention [58]. A number of studies using animal models have demonstrated that pBOO results in upregulation of pro-inflammatory cytokines such as IL-1β and increased bladder weight [2, 911]. Based on these findings, we speculate that a link exists between pBOO-associated mechanical insults, such as elevated intravesical pressure, and inflammation of the bladder tissue; however, no study to date has ever examined a link between elevated pressure and activation of the inflammasome.…”
Section: Introductionmentioning
confidence: 99%
“…If the inflammation-driven damage to the bladder reaches a state where fibrosis and nerve damage occur, symptoms can persist even after removal of the obstruction via surgical intervention [58]. A number of studies using animal models have demonstrated that pBOO results in upregulation of pro-inflammatory cytokines such as IL-1β and increased bladder weight [2, 911]. Based on these findings, we speculate that a link exists between pBOO-associated mechanical insults, such as elevated intravesical pressure, and inflammation of the bladder tissue; however, no study to date has ever examined a link between elevated pressure and activation of the inflammasome.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in many experimental species including rats, mice, rabbits, and guinea pigs show that fibrosis and inflammation are common factors in urinary bladder hypertrophy (Metcalfe et al, 2010). The cues that lead to fibrosis and inflammation in the urinary bladder are not clear, but have been suggested to involve a number of processes including but not limit to up-regulation of transforming growth factor (TGF)-β1 (Jiang et al, 2015, Zhang and Qiao, 2012), imbalance between matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) (Yang et al, 2013), mast cell accumulation (Michishita et al, 2015), ATP release from serosa (Shiina et al, 2016), oxidative stress and free radical damage (Lin et al, 2011b), and up-regulation of nerve growth factor (NGF) and other growth factors (Chung et al, 2010, Steers and Tuttle, 2006, Zhang and Qiao, 2012). Many of these cues are related to activation of the serine/threonine kinase Akt that serves as a central stage in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model, partial bladder outlet obstruction induced increased urothelial ATP release (47). In a prospective trial studying 79 male patients with BOO due to BPH and 22 asymptomatic controls, urinary ATP was significantly elevated in the BOO group, suggesting it could be used as a highly sensitive non-invasive biomarker of BOO (48).…”
Section: Biomarkersmentioning
confidence: 99%